Maternal Characteristics and Nutritional Status among First Trimester Pregnant Women in West Sumatera - Helmizar, Helmizar; Ferry, Ferdinal; Elda, Frima; Azrimaidaliza, Azrimaidaliza (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Optimizing the health and nutritional status of mothers during pregnancy can reduce the risk of stunting, with prevalence among children under five, in which the undernutrition condition was still high. It was about 24.4%. The research objective is to determine the association between maternal characteristics with nutritional status in the first trimester. This cross-sectional study involved 52 pregnant women in the first trimester. This study was conducted in the working area of health centers in Padang City 2022 which had a high prevalence of undernutrition problems. Data analysis was carried out using univariate tests and bivariate tests using chi-square with 95% CI and a significance level of p-value 0.05. The analysis results showed a significant relationship between BMI before pregnancy with nutritional status in the first trimester among pregnant women (p-value = 0.000). There is no relationship between education, occupation, age, and parity of the mother with nutritional status in the first trimester. Suggestions for pregnant women are to know their nutritional status, consume nutritious foods that are needed for fetal growth, and reduce the risk of low birth weight and stunting.